Noncoding RNAs regulate NF-κB signaling to modulate blood vessel inflammation - Cheng, Henry S.; Njock, Makon-Sébastien; Khyzha, Nadiya; Dang, Lan T.; Fish, Jason E. (Frontiers in Genetics, 2014)
Cardiovascular diseases such as atherosclerosis are one of the leading causes of morbidity and mortality worldwide. The clinical manifestations of atherosclerosis, which include heart attack and stroke, occur several decades after initiation of the disease and become more severe with age. Inflammation of blood vessels plays a prominent role in atherogenesis. Activation of the endothelium by inflammatory mediators leads to the recruitment of circulating inflammatory cells, which drives atherosclerotic plaque formation and progression. Inflammatory signaling within the endothelium is driven predominantly by the pro-inflammatory transcription factor, NF-κB. Interestingly, activation of NF-κB is enhanced during the normal aging process and this may contribute to the development of cardiovascular disease. Importantly, studies utilizing mouse models of vascular inflammation and atherosclerosis are uncovering a network of noncoding RNAs, particularly microRNAs, which impinge on the NF-κB signaling pathway. Here we summarize the literature regarding the control of vascular inflammation by microRNAs, and provide insight into how these microRNA-based pathways might be harnessed for therapeutic treatment of disease. We also discuss emerging areas of endothelial cell biology, including the involvement of long noncoding RNAs and circulating microRNAs in the control of vascular inflammation.